Capital Structure Management of Rice Farmers - Visperas, Arly N.; Magatas, Kimberly R.; Ambasing, Jackielou P.; Sia, Arianne Gayle R.; Aclera, Queen Alleah Rose A.; Soberano, Erica Mae A.; Eria, Jericho Q. (Future Science / FSH-PH Publications, 2025)
Capital structure management is a set of decisions related to the financing sources utilized in the entity's operation and development. Financing is a significant obstacle for smallholder farmers in accessing additional inputs required to boost agricultural yields and income. This study identified and measured the capital structure management of rice farmers, focusing on internal and external funding. This study is anchored to SDG 1, 2, 8, 12, 15 and 17. The quantitative-descriptive research design was used in this study and employed the convenience sampling method, wherein questionnaires were used to investigate the capital structure management of rice farmers in selected Barangays in Asingan, Pangasinan, Philippines specifically Barangay Bantog, Cabalitian, and Domanpot. The results indicated that most rice farmers are late middle-aged, married males who are classified as smallholder farmers, and have an average number of dependent family members. They sometimes practice capital structure management, which shows inconsistency in its implementation. The findings further revealed that rice farmers are risk-averse yet have stable financial conditions. Based on the data, this study recommended conducting a seminar about enhancing the capital structure management of rice farmers that highlights the significance of optimizing the rice farmers’ financial resources.